Thermographic Evaluation of the Effect of Three Bandage Products and Two Bandage Application Methods on Perfusion of the Equine Distal Extremity - Kobluk, C. N.; Walter, Patricia A.; Trent, A. Michelle; Libbey, C.; Salazar, R.; McCarville, Sally E. (Veterinary and Comparative Orthopaedics and Traumatology, 1990)
Thermography was used to evaluate the effects of the circulation on the distal equine limb of three wrapping materials (Vetrap® Tape, Equisport™ Equine Support Bandage (ESB) and 1680 denier experimental bandage). The wraps were applied at 100% stretch in a spiral or figure 8 technique. The Vetrap Tape and the ESB applied in a figure 8 technique were not statistically different from the control suggesting no circulatory impairment; however, the ESB and 1680 denier bandage wrapped in a spiral technique had a statistically significant effect suggesting circulatory impairment.Thermography was used to evaluate the effects of the circulation on the distal equine limb of three wrapping materials and two methods of application.
Keywords: Thermography; Circulation; Bandage